Information Technology and Its Role in Libraries and Information Centers - Jasim, Muntadher Oraibi; Hantoush, Ahmed Kadhim (South Asian Journal of Social Sciences and Humanities, 2023)
Aims research to identify the technology of modern used in libraries and information centers and areas that are used. These technologies impact on the information services provided by libraries. The research reached several conclusions, namely that there are a set of technologies used by libraries to perform their work, which have a positive impact on raising the level of services. The recommended search for some proposals which provide a suitable environment for the use of technical information in libraries and also work to raise the efficiency of human resources in libraries through Involve them in information technology courses to keep abreast of developments on the local and global levels.
Keywords: Information Technology; Libraries; Electronic Services